2018
DOI: 10.1016/j.ultsonch.2018.08.020
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different oils and ultrasound emulsification conditions on the physicochemical properties of emulsions stabilized by soy protein isolate

Abstract: The effects of different ultrasound emulsification conditions (20 kHz at 50-55 W cm, 40% amplitude for 2, 6, 12 or 18 min) on the physicochemical properties of soybean protein isolate-stabilized emulsions containing medium chain triglycerides (MCT), and long chain triglycerides (LCTs, palm, soybean and rapeseed oils) were investigated. It was found that MCT oil emulsions had the minimum droplet size (d) of 0.5 ± 0.0 µm after ultrasound emulsification for 18 min. Moreover, results indicated that MCT oil emulsio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
86
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 167 publications
(98 citation statements)
references
References 58 publications
6
86
0
Order By: Relevance
“…During sonication, the hydrophobicity of CAS changes, thanks to the different orientation of proteins at the oil-water interface, which can impact the ξ potential of emulsions formed by US treatment [46]. The impact of oil type on ξ potential, which is observed in our work, was also reported for soy bean protein isolate emulsions containing medium chain triacylglycerols, palm, soybean, and rapeseed oils after US treatment [47]. The lowering of ξ potential was ascribed to the formation of protein aggregates and different amounts of protein adsorbed onto emulsions containing studied oils of different compositions.…”
Section: Zeta Potentialsupporting
confidence: 77%
“…During sonication, the hydrophobicity of CAS changes, thanks to the different orientation of proteins at the oil-water interface, which can impact the ξ potential of emulsions formed by US treatment [46]. The impact of oil type on ξ potential, which is observed in our work, was also reported for soy bean protein isolate emulsions containing medium chain triacylglycerols, palm, soybean, and rapeseed oils after US treatment [47]. The lowering of ξ potential was ascribed to the formation of protein aggregates and different amounts of protein adsorbed onto emulsions containing studied oils of different compositions.…”
Section: Zeta Potentialsupporting
confidence: 77%
“…As established by Konuskan et al (2019), sunflower oil contains medium-chain fatty acids (C 16 to C 18 ) in higher amounts than rapeseed oil. Taha et al (2018) also suggested that lower molecular weight of the medium-chain triglycerides reduced more efficiently interfacial tension, thus contributing better for formation of a stable emulsion which might partially explain the higher negative values of DG, respectively the better stability of sunflower oil-in-water emulsions for all levels of oil and ERPI supplementations in present study (Table 1). Zorba and Kurt (2008) also observed dependence of selected meat emulsifying capacity and emulsion stability on the type of the plant oils used.…”
Section: Gibbs Free Energysupporting
confidence: 53%
“…It might be attributed to differences in oil composition and the specificities of the interaction between lipid molecules and proteins, although more experiments are needed to explain the exact mechanisms. Taha et al (2018) established that the content of adsorbed soybean protein in oil-in-water emulsions, containing medium-chain triglycerides and long chain triglycerides (palm, soybean and rapeseed oils), differed significantly. The same authors noted that mediumchain triglyceride emulsions contained thickest protein membrane around oil droplet that may explain why in this present study higher protein concentrations (0.5% and 1.0%) were needed for achieving more negative DG values of 5 and 10% sunflower oil-in-water emulsions.…”
Section: Gibbs Free Energymentioning
confidence: 99%
“…Unlike conventional emulsifying procedure, Kobayashi prepared monodispersed stable emulsion by using microchannel emulsification [33]. More researchers [34][35][36][37] used ultrasonic treatment to obtain small droplet size emulsion by benefiting from ultrasonic cavitation function [38]. It was reported that ultrasonic treatment can improve surface hydrophobicity, surface activity and protein aggregation.…”
Section: Introductionmentioning
confidence: 99%